واقع استخدام تقنيات الدفع الإلكتروني في المصارف السورية العامة دراسة تحليلية - القاضي, حسين; عبود, مادلين; سنكري, سهى (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف البحث إلى بيان أسباب تأخّر المصارف السورية عن تقديم خدمات الدفع الإلكتروني ،وبيان الصعوبات التي تواجهها هذه التقنيات، وتجاوزها. وقد أُجريت دراسة تحليلية لنظام الدفع الإلكتروني في المصرف العقاري، وقُورِن مع المصرف الصناعي، إذ رُكّز على بوابة الدفع الكترونية وآلية عملها والاستفادة منها، وعلى غرفة التقاص الإلكترونية، وخطوات مصرف سوريا المركزي بتطبيقها. كما حُلّلت الخدمات التقنية التي يقدّمها المصرف العقاري ، وكيف يُستفاد من تقنيات الاتصالات في مجال الخدمات المصرفية، وكيفة استخدم المصرف لأحداث البرمجيات لحماية العملاء من عمليات الاحتيال الإلكتروني. وقد اعُتمِد على بيانات مختلفة لإجراء عمليات التحليل إضافة إلى معلومات حُصل عليها من المختصين في المصارف المذكورة . و قد خلص البحث إلى أن أسباب التأخّر في استخدام الخدمات الإلكترونية تعود إلى عدم وجود بنية تحتية تخدم أنظمة الدفع، وقلّة موظفي قسم نظم المعلومات الذين يمتلكون الخبرة الكافية لتسيير هذه التقنيات .كما أنّ الروتين الوظيفي هو الذي يعيق تطور استخدام البرمجيات، ولكن بالرغم من الصعوبات التي يعانيها القطاع المصرفي إلاّ أنّ هناك أيدي عاملة سورية قادرة على مواكبة التطورات، والاستفادة من أحدث البرمجيات، ومن يطور موظفيه يتطور والعكس صحيح . The research aims at disclosing the reasons of Syrian banks delay in providing electronic payment and states the difficulties faced by these technologies and how they can overcome these difficulties. An analytical study of the electronic payment system in the Land Bank has been conducted and was compared with the Industrial Bank, where the focus was on the electronic payment gateway and mechanism of action and how to use them; the electronic clearing room and steps of the Central Bank of Syria should apply them as the technical services provided by the bank real estate were analyzed and how to make use of communication technologies in the field of banking services, and how the bank uses the latest software programs to protect customers from fraud mail. The reliance was on different data to perform analysis as well as information obtained from specialists in the banks mentioned. The research concluded that the reasons for the delay in the use of services is due to to the lack of infrastructure serving the payment systems and the lack of Information System Department staff who have sufficient experience to run these techniques; moreovere, it is the career routine that hinders the development of the use of the software, but in spite of the difficulties experienced by the banking sector, there are Syrian labors that are able to keep abreast of developments and make use of the latest software and how develop their staff develops and vice versa.